Synthesis of hafnium nanoparticles and hafnium nanoparticle films by gas condensation and energetic deposition - Michelakaki, Irini; Boukos, Nikos; Dragatogiannis, Dimitrios A.; Stathopoulos, Spyros; Charitidis, Costas A.; Tsoukalas, Dimitris (Beilstein Journal of Nanotechnology, 2018)
In this work we study the fabrication and characterization of hafnium nanoparticles and hafnium nanoparticle thin films. Hafnium nanoparticles were grown in vacuum by magnetron-sputtering inert-gas condensation. The as deposited nanoparticles have a hexagonal close-packed crystal structure, they possess truncated hexagonal biprism shape and are prone to surface oxidation when exposed to ambient air forming core–shell Hf/HfO2 structures. Hafnium nanoparticle thin films were formed through energetic nanoparticle deposition. This technique allows for the control of the energy of charged nanoparticles during vacuum deposition. The structural and nanomechanical properties of the nanoparticle thin films were investigated as a function of the kinetic energy of the nanoparticles. The results reveal that by proper adjustment of the nanoparticle energy, hexagonal close-packed porous nanoparticle thin films with good mechanical properties can be formed, without any additional treatment. It is shown that these films can be patterned on the substrate in sub-micrometer dimensions using conventional lithography while their porosity can be well controlled. The fabrication and experimental characterization of hafnium nanoparticles is reported for the first time in the literature.
Keywords: energetic deposition; hafnium; inert-gas condensation; nanomechanical properties; nanoparticles; nanoparticle thin films